Odpowiedzi

2010-03-04T18:50:31+01:00
6*(a+2b)-3*(2a-3b) =
6a + 12b - 6a + 9b =
21b

4*(b+3)+3*(a-b) =
4b + 12 + 3a - 3b =
b + 3a + 12

7*(b+c)-3*(b+2c) =
7b + 7c - 3b - 6c =
4b - c

5*(a+3)+2b-3*(a+b) =
5a + 15 + 2b - 3a - 3b =
2a - b + 15

6*(3+z)-4*(2z+4)+2*(8+z) =
18 + 6z - 8z - 16 + 16 + 2z =
18

-4*(2x-7-3y)-12*(-y-x) =
-8x + 28 + 12y + 12y + 12x =
4x + 24y + 28
2010-03-04T18:50:33+01:00
A)6a+12b-6a+9b=21b
b)4b+12+3a-3b=12+3a+b
c)7b+7c-3b-6c=4b+c
d)5a+15+2b-3a-3b=2a-b+15
e)18+6z-8z-16+16+2z=18
f)-8x+28+12y+12y+12x=28+24y+4x
2010-03-04T18:54:31+01:00
A)6*(a+2b)-3*(2a-3b)= 6a+12b-6a+9b= 21b
b)4*(b+3)+3*(a-b)= 4b+12+3a-3b=b+15
c)7*(b+c)-3*(b+2c)= 7b+7c-3b-6c=4b*c
d)5*(a+3)+2b-3*(a+b)= 5a+15+2b-3a-3b=2a+15-b
e)6*(3+z)-4*(2z+4)+2*(8+z)=18+6z-8z-16+16+2z=18
f)-4*(2x-7-3y)-12*(-y-x)= -8x+21+12y+12y+12x=4x+21+24y